A New View of Leisure - Ross, David (Relations industrielles / Industrial Relations, 1972)
The purpose of this paper is two-fold : first an attempt is mode to define work and leisure in operational terms. Second, using the new definitions of work and leisure, several problems in economies are re-examined and an attempt is mode to illustrate how the new definition may give us new insights into old and current problems.